2018
DOI: 10.1007/s10654-018-0473-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular mortality attributable to dietary risk factors in 51 countries in the WHO European Region from 1990 to 2016: a systematic analysis of the Global Burden of Disease Study

Abstract: This study was performed to highlight the relationship between single dietary risk factors and cardiovascular diseases (CVDs) in the WHO European Region. We used the comparative risk assessment framework of the Global Burden of Disease Study to estimate CVD mortality attributable to diet; comprising eleven forms of CVDs, twelve food and nutrient groups and 27 risk-outcome pairs in four GBD regions including 51 countries by age and sex between 1990 and 2016. In 2016, dietary risks were associated with 2.1 milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
100
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(110 citation statements)
references
References 36 publications
1
100
0
9
Order By: Relevance
“…In addition to lifestyle risk factors such as physical inactivity, unbalanced diet, smoking, alcohol, and obesity (Meier et al, 2019), genetic factors also play a pivotal role in CAD susceptibility (Musunuru and Kathiresan, 2019). Family and twin studies have demonstrated a strong genetic component of CAD, with heritability estimated between 40 and 60% (McPherson and Tybjaerg-Hansen, 2016;Khera and Kathiresan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to lifestyle risk factors such as physical inactivity, unbalanced diet, smoking, alcohol, and obesity (Meier et al, 2019), genetic factors also play a pivotal role in CAD susceptibility (Musunuru and Kathiresan, 2019). Family and twin studies have demonstrated a strong genetic component of CAD, with heritability estimated between 40 and 60% (McPherson and Tybjaerg-Hansen, 2016;Khera and Kathiresan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) are the rst cause of death in the world and impose enormous burden [1,2]. The role of genetic factors, physical activity, smoking and, nutrition in the prevention of CVDs is well known [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ряд ФР связан с привычками питания, важным аспектом, во многом определяющим здоровье человека, или, напротив, его нездоровье. Как показало недавнее исследование [2], в 2016г с нерациональным питанием только в Европейском регионе было ассоциировано ~2,1 млн смертей, 1,76 млн из которыхсердечно-сосудистые заболевания (ССЗ). Наибольший вклад в смертность от ССЗ внесли такие привычки, связанные с питанием, как недостаток в рационе цельного зерна (20,4%), орехов и семян (16,2%), фруктов (12,5%), морепродуктов (10,8%) и избыточное содержание натрия (12,0%).…”
Section: Introductionunclassified
“…Наибольший вклад в смертность от ССЗ внесли такие привычки, связанные с питанием, как недостаток в рационе цельного зерна (20,4%), орехов и семян (16,2%), фруктов (12,5%), морепродуктов (10,8%) и избыточное содержание натрия (12,0%). В некоторых странах вклад этих ФР растет, но есть страны (Израиль, Дания, Великобритания), где он значимо снижается [2].…”
Section: Introductionunclassified